Distinguishing Benign and Malignant Ovarian Tumors Preoperatively - Adhipurnawan Winarno, Gatot Nyarumenteng (Indonesian Journal of Obstetrics & Gynecology Science, 2024)
Ovarian cancer ranks as the fifth leading cause of cancer-related mortality among women globally. In 2020, there were approximately 314,000 reported cases of new ovarian cancer patients, resulting in an estimated 207,000 deaths.1 The highest incidence rates were observed in non-Hispanic white women, with 12.0 cases per 100,000 individuals, followed by Hispanics (10.3 per 100,000), non-Hispanic blacks (9.4 per 100,000), and Asian/Pacific Islander women (9.2 per 100,000). Disparities in access to healthcare services and treatment modalities contribute to varied mortality patterns, with the highest rates recorded among African populations. In Indonesia, ovarian cancer ranks as the third most prevalent cancer, comprising 7.84% of total cancers diagnosed in women.1 The heightened mortality rate observed in ovarian cancer can be ascribed to several factors including asymptomatic tumor growth, delayed manifestation of symptoms, and inadequate screening methods, ultimately resulting in diagnoses at advanced stages. Consequently, ovarian cancer is frequently described as a “silent killer”.2 To address diagnostic delays and reduce mortality rates associated with ovarian cancer, early detection and differentiation between benign and malignant ovarian tumors are crucial. This requires a comprehensive assessment comprising patient history, physical examination, and supporting investigation.